2015
DOI: 10.1177/0003489415576181
|View full text |Cite
|
Sign up to set email alerts
|

Altered Quality of Life and Psychological Health (SCL-90-R) in Patients With Chronic Rhinosinusitis With Nasal Polyps

Abstract: Olfactory dysfunction may have significant effects on QOL and psychological health. CRSwNP with anosmia is a distinct phenotype having mixed type of olfactory loss that might have a detrimental effect on depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…Two studies did not find any association between age and olfactory dysfunction . Within CRS‐specific factors, a higher Lund‐Mackay (LM) computed tomography (CT) score was most frequently associated with poorer smell with 11 studies reporting this relationship . Remaining studies did not examine this association.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Two studies did not find any association between age and olfactory dysfunction . Within CRS‐specific factors, a higher Lund‐Mackay (LM) computed tomography (CT) score was most frequently associated with poorer smell with 11 studies reporting this relationship . Remaining studies did not examine this association.…”
Section: Resultsmentioning
confidence: 98%
“…Six studies in CRS mixed and two studies in CRSwNP presented standard 16‐odor identification scores, yielding a population of 899 and 187 patients, respectively. Olfactory dysfunction using the 16‐odor Sniffin' Sticks identification test is defined as scores ≤11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies examined baseline medication usage, productivity, or physician visits, and found that comorbid depression was uniformly associated with worse performance across each of these metrics (Table 2). 7,9,17 Two studies 19,21 reported worse baseline olfaction in patients with CRS and depression, although one of these studies was limited to patients with CRS with nasal polyposis. 21 …”
Section: Factors Associated With a Positive Depression Screen Results mentioning
confidence: 99%